Hubungan Antara Fungsi Keluarga Dengan Status Gizi Anak Pada Murid Di Sd Negeri 5 Boyolali - GUMAWANG, ZULFIKAR ADI (2016)
Background : Family function is function had by family, that involves social, emotional, and health aspects. Family has important role to handle children nutritional status, because in family environment, children can maximize food intake also their growth and development. The lack of family roles in handling of children nutritional status, indicating the family function is unhealthy. The handling of children nutritional status is a health's problem that can be influenced by family function. Objectives : To analyze the relationship between family functioning and nutitional status. Methods : The research design is the analytic observational design with cross sectional analytic approaches. The research subjects were 60 students of SD Negeri 5 Boyolali who already fullfill the inclusion and exclusion criteria. Results : Respondents had healthy family functioning and good nutritional status with precentage 75,01 and minority respondents had not healthy family functioning and poor nutritional status with percentage 6,65. Based on fisher test, it shows the p value is 0,03, it means there is a relation between family functioning and children nutritional status. Conclusion : there is a significant relation between family functioning and children nutritional status